A magnetically drivable nanovehicle for curcumin with antioxidant capacity and MRI relaxation properties - Magro, Massimiliano; Campos, Rene [UNESP]; Baratella, Davide; Lima, Giuseppina [UNESP]; Hola, Katerina; Divoky, Clemens; Stollberger, Rudolf; Malina, Ondrej; Aparicio, Claudia; Zoppellaro, Giorgio; Zboril, Radek; Vianello, Fabio (Wiley-Blackwell, 2014)
Curcumin possesses wide-ranging anti-inflammatory and anti-cancer properties and its biological activity can be linked to its potent antioxidant capacity. Superparamagnetic maghemite (gamma-Fe2O3), called surface-active maghemite nanoparticles (SAMNs) were surface-modified with curcumin molecules, due to the presence of under-coordinated Fe-III atoms on the nanoparticle surface. The so-obtained curcumin-modified SAMNs (SAMN@curcumin) had a mean size of 13 +/- 4 nm. SAMN@curcumin was characterized by transmission and scanning electron microscopy, UV/Vis, FTIR, and Mossbauer spectroscopy, X-ray powder diffraction, bulk susceptibility (SQUID), and relaxometry measurements (MRI imaging). The high negative contrast proclivity of SAMN@curcumin to act as potential contrast agent in MRI screenings was also tested. Moreover, the redox properties of bound curcumin were probed by electrochemistry. SAMN@curcumin was studied in the presence of different electroactive molecules, namely hydroquinone, NADH and ferrocyanide, to assess its redox behavior. Finally, SAMN@curcumin was electrochemically probed in the presence of hydrogen peroxide, demonstrating the stability and reactivity of bound curcumin.
Keywords: antioxidants; curcumin; electrocatalysis; magnetic nanoparticles; MRI contrast agents